Discovering the Effect of Crossword on Grade Ten Students' Vocabulary Learning - Desta Saputri Sibuea; Deddy Suezdi (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
The purpose of this study is to find out whether or not there is significant effect of crosswords puzzles on Grade Ten Students’ Vocabulary Learning Outcome. The research method used in this research was quantitative true-experimental, and the design was post-test only control group design, meaning the data collected were only through post-test given to both experimental and control groups after treatments. To collect data for the study, the researcher used instrument in the form of objective, multiple choice , numbering 30 question items for both experimental class and control class that have been tried out in grade ten at experimental class. The scores obtained from the try-out class were used to analyze the validity, reliability, discrimination power and difficulty index of each question item in the instrument. The results of test obtained from samples were used to analyze the data using statistical formulas of Independent, t-test, preceded by normality and homogeneity tests as the pre-requisites to data analysis. The analysis using SPSS-based t-test produced significance (Sig.) score of 0.001, which was smaller than (<) Alpha 0.05, while the score of tobserved /to is higher than the score of t-table 4.10. Since the significance (Sig.) score of 0.001 is smaller than (<) Alpha 0.05, and the score of tobserved /to is higher than (>) the score of t-table 4.10, Ho is rejected and HA is accepted. Accordingly the research concludes that there is significant effect of crossword on grade ten students’ vocabulary learning. The keyword: crossword, vocabulary learning outcome